(untitled) - Donnelly, Mary Queen (Australia, 2005)
Skills for Consumer Success provides the users with information about their roles in the marketplace and how to sharpen their consumer skills. The text presents the process of opening a checking account, renting an apartment, applying for credit, looking for a job, buying a car, and paying taxes. Students learn the activities necessary for financial management and independence as they work through the text.
Keywords: English language; Textbooks for foreign speakers